Distribution of 0.2…4.5 keV plasma ions in set of U-2M discharges - Slavnyj, A.S.; Pavlichenko, R.O.; Shapoval, A.N.; Makhov, M.N.; Dreval, M.B. (Вопросы атомной науки и техники, 2021)
Charge exchange (CX) neutral fluxes were measured by neutral particle analyzer (NPA) in plasma discharges sustained by the W7-X-like radio frequency (RF) antenna in the Uragan-2M (U-2M) stellarator. CX fluxes in pure hydrogen discharge (B₀ = 0.36 T, f = 4.926 MHz) in stellarator configuration (effective perpendicular ion temperature T⊥ ≈ 450 eV) is less energetic in comparison with U-2M hybrid configuration (T⊥ ≈ 800 eV). RF discharge in stellarator configuration with helium and hydrogen mixture (B₀ = 0.351 T; f = 5.156 MHz, P = 6·10⁻⁴Torr) shows more energetic CX fluxes (T⊥ ≈ 1 keV). The ion cyclotron frequency distribution across the U-2M plasma has been studied numerically. These calculations are accompanied by direct measurement of the RF frequency by magnetic sensor. The ion cyclotron frequency is present in plasma bulk of all discharges under consideration. Потік нейтралів перезарядки вимірювався аналізатором нейтральних частинок у плазмових розрядах, що підтримуються радіочастотною W7-X-подібної антеною у стелараторі Ураган-2М (У-2М). Потоки нейтралів перезарядки в чисто водневому розряді (B₀ = 0,36 Тл, f = 4,926 МГц) у стелараторній конфігурації (ефективна перпендикулярна температура іонів T⊥ 450 эВ) менш енергійні в порівнянні з гібридною конфігурацією У-2М (T⊥≈ 800 эВ). ВЧ-розряд в стелараторній конфігурації з сумішшю гелію і водню (B₀ = 0,351 Тл; f = 5,156 МГц, P = 6 · 10⁻⁴Торр) показує більш енергійні потоки нейтралів перезарядки (T⊥ ≈ 1кэВ). Чисельний розрахунок розподілу іонної циклотронної частоти в плазмі У-2М, а також пряме вимірювання ВЧ частоти магнітним датчиком показують, що іонна циклотронна частота присутня в обсязі плазми всіх розглянутих розрядів. Поток нейтралов перезарядки измерялся анализатором нейтральных частиц в плазменных разрядах, поддерживаемых радиочастотной W7-X-подобной антенной в стеллараторе Ураган-2М (У-2М). Потоки нейтралов перезарядки в чисто водородном разряде (B₀ = 0,36 Тл, f = 4,926 МГц) в стеллараторной конфигурации (эффективная перпендикулярная температура ионов T⊥ ≈ 450 эВ) менее энергичны по сравнению с условиями гибридной конфигурации У-2М (T⊥ ≈ 800 эВ). ВЧ-разряд в стеллараторной конфигурации со смесью гелия и водорода (B₀ = 0,351 Тл; f = 5,156 МГц, P = 6 · 10⁻⁴Торр) показывает более энергичные потоки нейтралов перезарядки (T⊥ ≈ 1кэВ). Численный расчёт распределения ионной циклотронной частоты в плазме У-2М, а также прямое измерение ВЧ-частоты магнитным датчиком показывают, что ионная циклотронная частота присутствует в объёме плазмы всех рассматриваемых разрядов.